Antioxidant activities of sunflower protein hydrolysates treated with dual‐frequency ultrasonic: Optimization study. (7th May 2019) - Dabbour, Mokhtar; He, Ronghai; Mintah, Benjamin; Ma, Haile
Abstract: In this study, ultrasound pretreatments of sunflower‐meal protein (SMP) to yield high antioxidant capacity from its hydrolysates by response surface methodology were optimized. Optimization of experimental conditions was achieved to examine the impact of temperature, solvent‐solid ratio and sonication time on antioxidant capacities of SMP hydrolysates with Box–Behnken's design. Quadratic models of DPPH‐scavenging activity (DPPHSA), hydroxyl‐radical scavenging activity (HRSA), and Cu 2+ and Fe 2+ chelating activity (Cu 2+ ‐CA and Fe 2+ ‐CA) were developed, and their coefficients observed from multiple‐regression analysis. ANOVA indicated that time was highly significant ( p < .01) on all experimental responses. The best experimental point of DPPHSA, HRSA, Cu 2+ ‐CA, and Fe 2+ ‐CA was accessed at 42.50°C, 18.16 mL/g and 26.52 min and the predicted data for these responses were 52.09, 70.05, 50.85, and 43.35%, respectively. Outcome of verification experiment was reliable with predicted data for all responses. Additionally, DPPHSA, HRSA, Cu 2+ ‐CA, and Fe 2+ ‐CA of pretreated hydrolysate improved ( p < .05) by 17.41, 20.00, 14.72, and 26.41%, respectively over nonsonicated hydrolysate. Amino acid content and hydrophobicity of SMP hydrolysate at the optimum sonication condition were analyzed. Analyses indicated that ultrasonication could facilitate the releasing/unfolding of hydrophobic amino acids from SMP over nonsonicated samples during enzymolysis with high antioxidative capacity. Practical applications: Sonication pretreatment has been presented to have notable impacts on the antioxidant's capacities of protein hydrolysates. Sunflower‐meal protein is an abundant and low‐cost residue of oil industries, and is considered a potential bioactive peptides source, such as antioxidants. In this research, sonication pretreatment has been illustrated to be an effectual technique for the production of hydrolysates with antioxidant capacity from SMP. So, optimization of ultrasonication conditions is vital to examine the antioxidant capacities in SMP hydrolysates, which could be applied in large‐scale food system and future pharmaceutical activity research.